2014
DOI: 10.1007/s10517-014-2358-7
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation and Structural Reorganization of the Bladder Mucosa in Chronic Cystitis under Conditions of Ozone Therapy

Abstract: Structural reorganization of the bladder mucosa in chronic cystitis and its correction by ozone therapy were studied. A relationship between the epithelial layer restructuring of different kinds (dystrophy, metaplasia, and degeneration), level of cell proliferation, and ultrastructural organization of urotheliocytes was detected. This complex of structural reactions was combined with dysregulation of tissue bloodflow in the bladder mucosa, shown by laser Doppler flowmetry. Positive structural changes were most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Because of its various effects on the body, ozonetherapy has been evaluated for efficacy and applied in treatment of several disorders, including osteomyelitis [ 11 ], chronic obstructive pulmonary disease [ 12 ], hepatitis [ 13 ], cystitis [ 14 , 15 ], rheumatoid arthritis [ 16 , 17 ], OA [ 18 – 25 ], back pain [ 26 – 28 ], multiple sclerosis [ 29 ], peritonitis [ 30 ], osseous defects [ 31 , 32 ], and coronary arterial disease [ 33 ]. Intra-articular ozonetherapy has been successfully used in human medicine for treatment of inflammatory diseases, chronic and acute, synovitis, capsulitis, and OA [ 16 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its various effects on the body, ozonetherapy has been evaluated for efficacy and applied in treatment of several disorders, including osteomyelitis [ 11 ], chronic obstructive pulmonary disease [ 12 ], hepatitis [ 13 ], cystitis [ 14 , 15 ], rheumatoid arthritis [ 16 , 17 ], OA [ 18 – 25 ], back pain [ 26 – 28 ], multiple sclerosis [ 29 ], peritonitis [ 30 ], osseous defects [ 31 , 32 ], and coronary arterial disease [ 33 ]. Intra-articular ozonetherapy has been successfully used in human medicine for treatment of inflammatory diseases, chronic and acute, synovitis, capsulitis, and OA [ 16 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…That study agrees with the observations reported by Neimark et al evaluating the use of ozone in patients with chronic cystitis through microcirculation parameters and vesical morphological changes. The authors demonstrated a restructuring of the epithelial layer, with structural organization, reduction of the inflammatory process, and significant improvement of microcirculation in the bladder mucosa [ 28 ]. These observations may explain our results confirmed through the ICSI/ICPI scores.…”
Section: Discussionmentioning
confidence: 99%
“…The effects associated with moderate and transient oxidative stress triggered by ozone include the upregulation of the antioxidant system, homeostasis of NO, calcium, and inflammatory cytokines, and improvement in oxygen metabolism and immune modulation, as reported in clinical and preclinical studies [ 15 18 , 20 , 28 , 36 , 37 ]. Adverse reactions to ozone are mild and transient, contributing to the growing interest in its use in various pathologies, including IC/BPS.…”
Section: Discussionmentioning
confidence: 99%
“…Total ozone dose is equal to the product of gas volume (ml) and ozone concentration (µg/ml). According to the European Union, the ozone generators are treated as sanitary products possessing II-b quali ication, and it should be registered with a known entity under a noti ied manufacturer (Neimark et al, 2014). Compared to oxygen, ozone is more powerful oxidant; practically, it can oxidise various non-organic and organic compounds.…”
Section: Introductionmentioning
confidence: 99%